Mulching Herbs, Vegetables and Fruit Trees in The Florida-Friendly Edible Landscape - Tina McIntyre; Rachel Gutner; Tiare Silvasy; Jacqlyn Rivas; Esen Momol (EDIS)
Mulching is the practice of spreading material around the base of a plant to protect the plant, conserving moisture or suppressing weeds. This new 7-page publication of the UF/IFAS Environmental Horticulture Department serves as a guide for homeowners and professionals to reference best practices on mulching and discusses mulch sources, application techniques, and management practices. It will clarify the mulch needs of fruit trees, shrubs, herbs, and vegetables to promote plant health. Written by Tina McIntyre, Rachel Gutner, Tiare Silvasy, Jacqlyn Rivas, and Esen Momol. https://edis.ifas.ufl.edu/ep625